Brand Platform in the Professional Sport Industry Sustaining Growth through Innovation - Zheng, Jingxuan (Springer International Publishing, 2018)
This book examines how the emergence of new media brings brought challenges to the North American sport industry, discussing challenges in terms of a shift from an information economy to an attention economy perspective. Historically, the arrival of new forms of media, including radio and television, were not universally supported by sports leagues, wary of existing industry relationships with stakeholders, and new media have made the multi-sided market model of professional sports leagues - which has focused on protection and exploitation of league content - inefficient, and calls for a new model to integrate new media into the market. By integrating platform theory with the Service Dominant Logic (SDL) of marketing we describe how the multi-sided market of professional sports is evolving into a platform ecosystem, and the role of its most important customers - the fans - will also evolve from end users, to value co-creators, complementors and innovators. This book will create a new way of understanding the evolution of professional sports leagues and future growth of the industry, and lay the foundation for new research within the academic realm of sport management and sports marketing.